1992
DOI: 10.1111/j.1365-2044.1992.tb04210.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paracetamol or diclofenac administered before operation on postoperative pain and behaviour after adenoidectomy in small children

Abstract: SummaryWe compared the effects of rectally administered diclofenac (12.5 mg) with paracetamol (12s mg) on pre-and postoperative behaviour and the need for supplementary analgesia in 44 children scheduled for adenoidectomy (with or without myringotomy). The study drugs were given in combination with diazepam (0.5 mg.kg-') about 20 min before the children were taken to the operating theatre. On arrival there, the children who had received diclofenac were significantly quieter ( < 0.05), easier to handle ( p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 14 publications
1
43
0
4
Order By: Relevance
“…In a comparative study involving oral diclofenac (12.5 mg) and acetaminophen (125 mg), the diclofenactreated children demonstrated decreased preoperative restlessness, crying in response to handling, and a reduced postoperative meperidine requirement (36). In a placebo-controlled study involving children undergoing placement of ear tubes, the preoperative administration of oral ketorolac (1 mg/kg in cherry syrup) resulted in lower pain scores and a decreased requirement for supplemental analgesics in the postoperative period compared to acetaminophen (10 mg/kg) (37).…”
Section: Preoperative Use Of Nsaids In Childrenmentioning
confidence: 98%
“…In a comparative study involving oral diclofenac (12.5 mg) and acetaminophen (125 mg), the diclofenactreated children demonstrated decreased preoperative restlessness, crying in response to handling, and a reduced postoperative meperidine requirement (36). In a placebo-controlled study involving children undergoing placement of ear tubes, the preoperative administration of oral ketorolac (1 mg/kg in cherry syrup) resulted in lower pain scores and a decreased requirement for supplemental analgesics in the postoperative period compared to acetaminophen (10 mg/kg) (37).…”
Section: Preoperative Use Of Nsaids In Childrenmentioning
confidence: 98%
“…[24] Our study finding were in contrast with finding of Baer and his colleagues who demonstrated that children receiving preoperative rectal diclofenac sodium needed fewer supplementary doses of postoperative pethidine compared to those who received pre-operative rectal paracetamol. [25] Paracetamol is an effective antipyretic at plasma concentration of 0.066-0.130 mmol/L. [17,26,27] In our study, body temperature of children also had decreased significantly in Gr.…”
Section: Discussionmentioning
confidence: 51%
“…Literature review showed worldwide up to 70% of patients receive ineffective, inadequate or delayed postoperative pain relief. 5 In postoperative period, multimodal analgesia strategy is used to obtain maximum pain relief with minimum side effects. Combination of paracetamol and/or NSAIDS, opioids and local anaesthetics through regional anaesthesia are component of multimodal analgesia.…”
Section: Discussionmentioning
confidence: 99%